Dispute Resolution in Mixed Marriages Under the Perspective of Private International Law in Indonesia - Said Muhammad Nadhif Said; Yati Sharfina Desiandri; Hilbertus Sumplisius M. Wau (Ultimate Journal of Legal Studies, 2026)
Mixed marriage is a legal phenomenon that continues to increase along with globalization, international mobility, and interactions between citizens of different countries. Such marriages often give rise to legal issues related to citizenship, marital property, child custody, inheritance, and the determination of applicable law. This study aims to analyze the settlement of disputes arising from mixed marriages within the framework of Private International Law in Indonesia. The research uses a normative juridical method through the examination of legislation, legal doctrines, and relevant literature. The findings indicate that Indonesia applies several connecting factors, including nationality, domicile, and legal principles recognized in Private International Law to determine the applicable law in mixed marriage disputes. However, legal uncertainty remains due to the absence of a comprehensive codification of Private International Law in Indonesia. Therefore, legal reform is necessary to provide certainty, justice, and legal protection for parties involved in mixed marriages. The study concludes that strengthening regulations and harmonizing legal principles are essential to effectively address cross-border family law disputes